2021
DOI: 10.3390/app11020667
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Routing Optimisation in Humanitarian Operations: A Survey on Modelling and Optimisation Approaches

Abstract: The growing field of humanitarian operations is driven by frequent events of disasters seen in the world today. Within this field, Operations Research (OR) plays a critical role in alleviating the suffering of victims that are impacted by disasters. This paper focuses on the branch of a well-known OR problem, known as the Vehicle Routing Problem (VRP), within the selected scope of humanitarian operations. A total of 123 papers of the last decade are reviewed and classified under the humanitarian operations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 142 publications
0
13
0
2
Order By: Relevance
“…Anuar vd. [27], çalışmalarında afetten etkilenen insanlara yardım edebilmek amacıyla araç rotalama problemine odaklanılmıştır. Kokaji ve Kainuma [28], çalışmalarında afet sonrası yardım malzemelerinin eşit ve adil dağıtımının sağlanması için matematiksel model oluşturulmuştur.…”
Section: Yöntemler (Methods)unclassified
“…Anuar vd. [27], çalışmalarında afetten etkilenen insanlara yardım edebilmek amacıyla araç rotalama problemine odaklanılmıştır. Kokaji ve Kainuma [28], çalışmalarında afet sonrası yardım malzemelerinin eşit ve adil dağıtımının sağlanması için matematiksel model oluşturulmuştur.…”
Section: Yöntemler (Methods)unclassified
“…Different combinations and variations of these problem characteristics are especially addressed by the humanitarian operations applications. The review paper [11] had shown that those addressing split delivery VRP would also typically incorporate a multi-trip operation as a means to address the vehicle limitation problem during such a chaotic time. This could also be seen in [12][13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for works that addressed both multi-depot and multi-trip operations, this is seen in [19]. For a more in-depth, rich VRP that incorporates multi-depot, split delivery, multi-trip and road capacity for the application of humanitarian operations, refer to the work in [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations